OBSERVATION OF COSMIC-RAY ANISOTROPY WITH THE ICETOP AIR SHOWER ARRAY - Aartsen, M. G.; Abbasi, R.; Abdou, Y.; Ackermann, Markus; Adams, J.; Aguilar, J. A.; Ahlers, M.; Altmann, D.; Andeen, K.; Auffenberg, J.; Bai, X.; Baker, M.; et al. (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2013)
The astrophysical journal 765(1), 55 (2013). doi:10.1088/0004-637X/765/1/55 : We report on the observation of anisotropy in the arrival direction distribution of cosmic rays at PeV energies. The analysis is based on data taken between 2009 and 2012 with the IceTop air shower array at the south pole. IceTop, an integral part of the IceCube detector, is sensitive to cosmic rays between 100 TeV and 1 EeV. With the current size of the IceTop data set, searches for anisotropy at the 10–3 level can, for the first time, be extended to PeV energies. We divide the data set into two parts with median energies of 400 TeV and 2 PeV, respectively. In the low energy band, we observe a strong deficit with an angular size of about 30° and an amplitude of (– 1.58 ± 0.46stat ± 0.52sys) × 10–3 at a location consistent with previous observations of cosmic rays with the IceCube neutrino detector. The study of the high energy band shows that the anisotropy persists to PeV energies and increases in amplitude to (– 3.11 ± 0.38stat ± 0.96sys) × 10–3. : Published by Univ.11032, Chicago, Ill. [u.a.]